Metode Buffer Index Untuk Menentukan Volum Tangki Pada Proses Netralisasi Air Limbah - Siti Agustina; Emmy Ratnawati (Jurnal Kimia dan Kemasan, 1995)
We often found that industrial waste water have low or high pH; therefore it should be adjust to neutral before discharging into river or sea. We can treat it by neutralization to get no pH. There are many factors that affect eutralization process. One of them is retention time the reaction tank. Research has been done by using artificial waste water which is hydrochl acid solution (0,025N) and acetic acid solution (0,025 N). Sodium hydroxide (0,5 N) and Sodzz; carbonate (0,8 N) solution were used as an alkali. By using neutralization equipment, retention time will produce smaller pH fluctuation; and the bigger buffer index the smaller, fluctuation. The relationship among retention time, pH fluctuation and buffer index, will help to design volume of the reaction tank for continous neutralization that treat heavy containing waste water using pH control.